IMPLEMENTATION OF CRIMINAL SANCTIONS FOR THE CRIMINAL ACTION OF FRAUD AGAINST CONSUMERS RELATED TO THE SALE SYSTEM BASED ON LAW NO. 8 OF 1999 CONCERNING CONSUMER PROTECTION - Kholim, Nur; Lestari, Helsi Febri (Universitas Islam Lamongan, 2023)
This research was conducted to find out the criminal sanctions for the crime of selling sales and to find out the responsibilities of business actors and the efforts of consumers who are harmed by sale and purchase transactions that are deceptive and misleading in terms of Law no. 8 of 1999. which is associated with the Bandung District Court Decision Number 930/Pid.Sus/2021/PN.Bdg. This study uses a normative juridical research method, namely the legal research method of literature which is carried out by examining library materials or secondary materials. The results of the study show that the application of law and criminal sanctions is in accordance with the provisions of Article 62 paragraph (2) in conjunction with Article 11 letter b of Law no. 8 of 1999 concerning Consumer Protection by imposing criminal sanctions on the defendant in the form of imprisonment for 8 (eight) months. Sentence is carried out as a preventive and repressive effort that is educative, constructive and motivational so that the defendant does not commit the act again in the future. Meanwhile, the responsibility of business actors in fraud cases can be in the form of liability for criminal sanctions in the form of imprisonment or fines and can also be in the form of civil matters such as replacement of compensation.